RELIGIOUS MODERATION IN WATER USE PRACTICES BASED ON BULUGH AL-MARAM AT SALAF ISLAMIC BOARDING SCHOOLS: A Study of Living Hadith - Nurudin, Muhamad; Saerozi, Ahmad; Rochmah, Zahrotur (RIWAYAH, 2022)
This study is motivated by the increasing urgency of religious moderation in a plural society amid the growing crisis of water resources, particularly within Islamic boarding schools (pesantren). Bulugh al-Maram, as a primary reference for hadith ahkam studied in pesantren, holds significant potential for fostering values of moderation, especially through hadiths regulating proportional and efficient water use. However, a purely textual understanding of certain hadiths may also lead to rigid or even radical attitudes if not properly contextualized. Therefore, this research aims to examine the values of religious moderation embedded in the hadiths on water usage in Bulugh al-Maram and their implementation in Salaf pesantren along the northern coast of Java. This study employs a qualitative research method using both library and field approaches within the framework of living hadith studies. Hermeneutic analysis is applied to interpret the hadith texts, while field data are collected through observations and interviews conducted in several Salaf pesantren in Kudus and its surrounding areas. The findings reveal that Bulugh al-Maram contains numerous hadiths that promote moderate religious attitudes, such as prohibitions against excessive water use (israf), flexibility in purification practices, and recognition of diversity in ritual observance. These values are reflected in pesantren practices, including water-saving behaviors, the use of tayammum when appropriate, and tolerant attitudes toward differences among Islamic legal schools. This study recommends strengthening contextual approaches to hadith understanding through living hadith studies so that the values of religious moderation can be more effectively internalized, while simultaneously contributing to water resource conservation and the promotion of social harmony within pesantren communities.  [Penelitian ini dilatarbelakangi oleh semakin menguatnya urgensi moderasi beragama di tengah masyarakat plural serta krisis energi air yang kian mengkhawatirkan, khususnya di lingkungan pesantren. Kitab Bulugh al-Maram sebagai rujukan utama hadis-hadis ahkam di pesantren memiliki potensi besar dalam menanamkan nilai moderasi, terutama melalui hadis-hadis yang mengatur penggunaan air secara proporsional dan efisien. Namun, pemahaman tekstual terhadap hadis-hadis tertentu juga berpotensi melahirkan sikap kaku bahkan radikal jika tidak dikontekstualisasikan. Oleh karena itu, penelitian ini bertujuan mengkaji nilai-nilai moderasi beragama dalam hadis penggunaan air dalam Bulugh al-Maram serta implementasinya di pesantren salaf di wilayah Pantura Jawa. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan dan lapangan (living hadis). Analisis hermeneutik digunakan untuk menafsirkan teks hadis, sementara data lapangan diperoleh melalui observasi dan wawancara di beberapa pesantren salaf di Kudus dan sekitarnya. Hasil penelitian menunjukkan bahwa Bulugh al-Maram memuat hadis-hadis yang mendorong sikap moderat, seperti larangan israf dalam penggunaan air, fleksibilitas dalam bersuci, serta pengakuan terhadap keragaman praktik ibadah. Implementasi nilai-nilai tersebut tampak dalam praktik penghematan air, pemanfaatan tayamum, serta sikap toleran terhadap perbedaan mazhab di pesantren. Penelitian ini merekomendasikan perlunya penguatan pemahaman kontekstual hadis melalui kajian living hadis agar nilai moderasi beragama dapat terinternalisasi secara lebih efektif, sekaligus berkontribusi pada upaya konservasi sumber daya air dan penguatan harmoni sosial di lingkungan pesantren]